Carbon Capture and Storage (CCS) in Nigeria: A Review of Challenges and Opportunities (British Journal of Multidisciplinary and Advanced Studies, 2024)
Carbon Capture and Storage (CCS) is crucial for mitigating climate change by capturing and storing CO₂ emissions from industrial processes and power generation. This paper reviews the challenges and opportunities of implementing CCS in Nigeria, based on literature from 2014 to 2024. Key challenges include technical barriers like inadequate infrastructure and limited expertise, economic constraints due to high costs, and regulatory issues from the lack of a comprehensive legal framework. Public perception and awareness also pose significant social challenges. However, Nigeria has substantial opportunities for CCS due to its geological potential for CO₂ storage in depleted oil and gas fields and saline aquifers. Economically, CCS can create jobs, stimulate technological innovation, and position Nigeria as a CCS leader in Africa. Environmentally, CCS can significantly reduce greenhouse gas emissions. The paper concludes with policy recommendations, including subsidies, tax incentives, and a robust regulatory framework, to promote CCS in Nigeria. It emphasizes the need for investments in research and development, public-private partnerships, and effective public engagement strategies to address challenges and harness opportunities, contributing to global climate change mitigation and sustainable development.